"Nonempty" Gap Between Radiation Belts: The First Observations. (17th December 2013) - Panasyuk, Mikhail
Abstract : The first space experiments carried out in 1958 by the scientific groups of James Van Allen (United States) on board the first Explorer satellites and Sergey Vernov (Soviet Union) on board the satellite Sputnik 3 led to the discovery of the Earth's radiation belts—the particles (mainly protons and electrons) captured by the magnetic field of the Earth. Two scientific groups independently came to the conclusion that the electrons in the geomagnetic trapping region fill two areas, inner and outer radiation belts, unlike the protons, which fill the whole trapping region [see, e.g., Lemaire, 2000].